2021
DOI: 10.1111/ijcp.14435
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the need for pharmacogenomics education among pharmacists in the West Bank of Palestine

Abstract: Background Pharmacogenomics testing aims to optimise therapy and reduce the inter‐individual variation in drug response. One of the major barriers against the implementation of pharmacogenomics testing is the low level of knowledge on the topic. Aims This study aimed to evaluate the need for pharmacogenomics education among pharmacists in the West Bank of Palestine. Methods This study was cross‐sectional and included 370 pharmacists, among different cities in the West Bank of Palestine between October and Dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…These findings among healthcare providers in the UAE are consistent with those in other Middle Eastern countries. Similar results were reported in Jordan [10], the West Bank of Palestine [11], Egypt [12], and Qatar [13], where all participating pharmacists had poor knowledge but highly positive attitudes regarding pharmacogenomic testing. These findings indicate that there is a demand to improve knowledge about pharmacogenomic testing among pharmacists and other healthcare providers in Middle Eastern Arabic countries.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…These findings among healthcare providers in the UAE are consistent with those in other Middle Eastern countries. Similar results were reported in Jordan [10], the West Bank of Palestine [11], Egypt [12], and Qatar [13], where all participating pharmacists had poor knowledge but highly positive attitudes regarding pharmacogenomic testing. These findings indicate that there is a demand to improve knowledge about pharmacogenomic testing among pharmacists and other healthcare providers in Middle Eastern Arabic countries.…”
supporting
confidence: 80%
“…These surveys of the attitudes toward and knowledge and practice of pharmacogenomic testing in Middle Eastern countries were conducted recently, and pharmacogenomic testing is still not implemented in clinical practice in these countries. The lack of pharmacogenomics knowledge and training appears to be the major obstacle to the implementation of pharmacogenomic testing in clinical practice in the Middle East, including the UAE [6,11,12,14]. Some universities in the UAE and Qatar have recently established science departments providing graduate certificates in pharmacogenomics and PM.…”
mentioning
confidence: 99%
“…It was also found that more than two-thirds of the community pharmacists could not identify clopidogrel and pantoprazole as medications that need pharmacogenomics testing while one-third could not identify paroxetine, simvastatin and warfarin. This result is supported by a study conducted among Palestinian pharmacists which showed that more than two-thirds are not aware of medications that require pharmacogenomics testing [ 32 ]. Inadequate knowledge of pharmacogenomics can be attributed to lack of previous pharmacogenomics training among the respondents as less than one-third of the respondents in this study had previous training.…”
Section: Discussionmentioning
confidence: 70%
“…Such studies highlight the significance of pharmacogenetics research, particularly in the Middle East, where the lack of such data and awareness hinders the implementation of pharmacogenomics into practice [ 150 ].…”
Section: Pharmacogenomics and The Mena Regionmentioning
confidence: 99%